The effect of space flight on genes expression in brain - A. S. Tsybko; T. V. Ilchibaeva; N. K. Popova (Вавиловский журнал генетики и селекции)
Many serious adverse physiological changes occur during spaceflight, primarily due to microgravity. In search of underlying mechanisms, many experimental tools have been developed, ranging from microgravity modeling on Earth to space flight investigations, part of which is to study the expression of genes and proteins. Unlike bone and muscle tissue, molecular changes in nerve cells during spaceflight are practically unexplored. This review aims at summarizing the recent advances in identifying gene and protein expression changes of nervous system cells under microgravity conditions. To a large extent, this review will focus on the results of the Bion-M1 biosatellite. We have for the first time revealed dopamine and serotonin microgravityresponsive genes (tyrosine hydroxylase, catechol-Omethyltransferase, and D1 receptor in the nigrostriatal system; D1 and 5-HT2A receptors in the hypothalamus; and monoamine oxidase A in the frontal cortex). Decreased genetic control of the dopamine system may contribute to the spaceflight-induced locomotor impairment and dyskinesia described for both animals and humans. Also, the system of neuronal apoptosis is activated under the influence of microgravity as evidenced by changes in the expression of antiapoptotic protein Bcl-XL in the hippocampus and hypothalamus. The long spaceflight produced dysregulation in the genetic control of genes encoding GDNF and CDNF neurotrophic factors. Because they play a crucial role in the protection and maintenance of dopaminergic neurons, reducing their expression may be one of the reasons for the negative impact of spaceflight on the brain dopamine system. Thus, the data obtained from the flight of the Bion-M1 biosatellite for the first time allowed for creating a molecular genetic basis for the currently known neurophysiological mechanisms of adaptation of the central nervous system to the state of weightlessness.